Arterial stiffness as a screening tool for cardiovascular risk in health and disease - Vidya Ganji; A Sowganthikashri; Madhuri Taranikanti; M Kalpana; U Madhusudhan; Archana Gaur; Nitin A. John (Journal of Family Medicine and Primary Care, 2024)
Background: Cardiovascular diseases (CVD) account for approximately one-third of all deaths worldwide. The incidence of cardiovascular events such as myocardial infraction has been reported to be progressively increasing with age, especially with existing comorbidities such as hypertension, diabetes and obesity. Assessing arterial stiffness indices may serve as a screening tool in identification of population at risk of cardiovascular diseases and assist in implementation of preventive measures and early treatment in this population. Objectives: To measure and compare the arterial stiffness indices in healthy adults with diabetes, hypertension and obesity. Methods: A total of 184 adults in the age group of 30-50 years were included in the study who were divided into 4 groups: Group I (n = 64) (diabetic), group II (n = 40) (hypertensives), group III (n = 40) (obese) and group IV (n = 40) (control). The arterial stiffness indices were measured by using a certified oscillometric device in all the participants. Results: The arterial stiffness indices were assessed by using a certified oscillometric device in all the participants. The mean values of right baPWV and left baPWV are found to be significantly higher in hypertensive subjects compared with obese, diabetic and healthy controls. Conclusion: The pulse wave velocity, ASI and pulse pressure serve as independent predictors of cardiovascular mortality and outcomes in hypertension, diabetes and obesity as well as healthy individuals.